بیع کے اختلال رضا میں کچھ غیر معروف خیارات اور اکراہ کے احکامات کا ایک جائزہ: A Descriptive Survey of Shariah Orders of unconventional options, and Compulsion in the trade for disruption of Raza - Shafi , Dr. Hafiz Khalid; Muhammad Asif , Dr. Hafiz Khair (Journal of Quranic and Social Studies, 2022)
Every buyer and seller in trade is made to agree on terms and conditions, none of them can walk away from the contract after Ijab and Qabool, but every buyer and Seller have to walk away from this deal if they set a certain agreement or Shariah gives them relief itself to break the deal. A mutual consensus is needed for any trade agreement. On the time of Contact both parties are willing on the deal, after that by using the Option (Khiaar) breaking this deal shows that one party is unwilling to continue this trade , like wise agroy compulsion trade does not have mutual agreement also. Compulsion (Ikrah) has different Islamic obligations due to its nature of disagreement. This Article discusses different non Famous options of trade and Special orders on Compulsion due to its unusual nature. This article discusses this topic in detail